Correlação entre cortisol pós-ACTH, variáveis diagnósticas e a posologia do trilostano em cães portadores de hipercortisolismo ACTH dependente - Gouvêa, Fernanda Nastri (2022)
Trilostane is considered a great therapy to manage canine pituitary-dependent hypercortisolism (PDH). Dosage divergences associated with the risk of iatrogenic hypocortisolism have caused delays in disease control and the need to perform a sequence of hormonal tests with a relatively high cost and time for dose adjustment, since most individuals end up requiring additions to achieve control of hypercortisolism. The lack of more concrete therapeutic perspectives generates anxiety in the entire team involved with the patient's treatment, when the tutors give up the treatment or do not carry out the correct dose adjustment protocol, jeopardizing the effectiveness of the treatment and the patient's health. Based on the fact that the ACTH stimulation test provides information about the ability of the adrenals to respond to a stimulus for cortisol secretion, this study aimed to correlate the post-ACTH cortisol value in the diagnosis of HPD with the final dose. of trilostane needed to achieve endogenous cortisol control in dogs, assuming that the higher the post-ACTH serum cortisol concentration, the higher the dose of trilostane needed to control the disease. For this, 67 medical records of dogs with HPD had the data from laboratory tests, imaging and cortisol value at diagnosis tabulated and correlated with the dose required to achieve normocortisolemia. The odds analysis showed that for each unit of increase in the thickness of the right caudal adrenal pole within the categories established according to weight ranges, there is 8.861 times more chance of the patient to have post-ACTH cortisol values ≥ 27 at diagnosis. . Independently, dogs that have post-ACTH cortisol ≥ 27 μg/dL also at diagnosis are 33.5% more likely to need higher doses of trilostane to control hypercortisolism. Therefore, post-ACTH cortisol correlates with both the size of the right adrenal gland and the final dose of trilostane for the control of HPD in dogs.